Comparative effects of two ozonation treatments on wheat flour technological properties - Saint Paul, Julien (Kansas State University, 2007)
Ozone, a triatomic form of oxygen with a Generally Recognized As Safe (GRAS) status from the U. S. Food and Drug Administration, is a strong antimicrobial and sanitizing agent with numerous potential applications in the food industry. One of them is the improvement of wheat flour baking qualities, by replacement of the actual chlorination treatment. Following recent developments realized by the company Goemar (France) which invented and patented an ozone treatment device for wheat grain and a method for making flour from ozone-treated grains, this study aims to determine the effect of ozone treatment on wheat grain and on wheat flour, and to compare them. Three different ozone concentrations with different application times rendering three quantities of absorbed ozone have been investigated. Rheological, physicochemical and baking properties of soft wheat flours stemming from both treatments were evaluated and compared to untreated flour. Results were overall significant and showed that the treatment of flour gives more marked results than the treatment on grain for retention capacity in sucrose and volume of cakes but decreases the [alpha]-amylase activity. On the other hand, action of ozone on grain augments the maximum viscosity of the flour. Bread volume was found to be increased by both treatments in similar proportions. The treatments were also analyzed in particular and showed specific characteristics. A single treatment has not been determined to enhance all characteristics of the flour. Hence, the modification of precise features of the flour has to be related to a specific treatment.
Keywords: Ozonation; Wheat flour; Chlorination; Agriculture, Food Science and Technology (0359)